Development of Local Wisdom-Based Puzzle Media to Improve Early Reading Skills of Grade II Students at SDN 04 Koto Baru - Asmaryadi, Ahmad Ilham; Hader, Antik Estika; Sartika, Mia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study is motivated by the lack of engaging learning media at SD 04 Koto Baru, which has led to students showing low interest in participating in the learning process. An effort to overcome this issue involves the use of supportive learning tools that can attract students' attention specifically, the use of puzzle media. The objectives of this research are: to develop a valid puzzle media for early reading skills, to develop a practical puzzle media based on local wisdom to improve early reading, and to develop an effective puzzle media based on local wisdom to enhance early reading. This study is a type of research and development using the ADDIE development model, which consists of the stages: Analyze, Design, Development, Implementation, and Evaluation. The analysis stage includes needs analysis, curriculum analysis, media analysis, children's characteristics analysis, and material analysis. The design stage involves content design and media layout. The development stage includes validity testing; the implementation stage consists of practicality and effectiveness testing conducted at SD 04 Koto Baru, Dharmasraya Regency; and the evaluation stage assesses the overall results. The validation results from three experts indicate an average score of 91.06%, categorized as very valid. The practicality test achieved an average score of 100%, categorized as very practical. The effectiveness test, conducted with 25 students, yielded an average score of 81%, falling into the category of very effective. Based on the above results, it can be concluded that the puzzle media based on local wisdom for early reading supports students in better understanding the learning process. This research has produced a puzzle-based learning medium that is highly valid, highly practical, and highly effective.